Determination of Plasmodial Species Prevalence among Patients Received at Cotonou Boni Clinic during Rainy Season in the Year 2022 - Tokponnon, Tatchémè Filémon (My University, 2023)
Aims: Malaria is a life-threatening disease caused by parasites transmitted by bites from infected female anopheles. It is a preventable and treatable illness. It remains a recurring disease among public health diseases that exposes many people to a risk of infection, including children under the age of 05 in Benin. Methods: To determine the prevalence of malaria and different plasmodial species at the Dr Pierre BONI Clinic, we performed venous and capillary samples on 731 patients for the realization of thick drops and blood smears between June and July 2022. Results: Three plasmodial species were identified in 228 patients (31%) as malaria of the 731 patients included in the study with 3 species of plasmodium found: Plasmodium falciparum (95.5%), Plasmodium malariae (2.85%), Plasmodium ovale (1.65%). Mixed or double species was also recorded in some patients: Plasmodium falciparum+ Plasmodium malariae and Plasmodium falciparum+ Plasmodium ovale. The majority of patients have the presence of trophozoites at Plasmodium falciparum, 95.5%. The parasitic density of P. falciparum is higher than that of P. malariae and that of P. ovale. Conclusion: Although evaluated during a period of low transmission, malaria remains a real public health problem. The distribution of the disease is closely related to the presence in the blood of plasmodial species.
Keywords: Malaria; plasmodium ovale; plasmodium falciparum; plasmodium malariae; cotonou.